A preliminary checklist of molluscs in the Kelanang coast at Banting: an observational study - Abdul Rahman, Mohd Nordin; Ismail, Mohamad Saupi; Ahmad Wakid, Sarini; Wan Solahudin, Wan Mohd Syazwan; Abd Aziz, Nor Azwady; Mustafa, Muzkhali; Okamura, Hideo; Horie, Yoshifumi; Ong, Meng Chuan; Dwi Setyawan, Ahmad; Kumar, Krishnan; Cheng, Wan Hee; et al. (SciRes Literature LLC, 2023)
This research aims to determine the updated species list of molluscs (Gastropods and Bivalves) populating the Kelanang coast at Banting (Selangor) in November 2022. Nine gastropod species and eight bivalve species were discovered in this study, with Pisania striata, Cominella quoyana, and Mereterix casta as the dominant species. This preliminary investigation could provide a continuous baseline for future taxonomical and biodiversity references as part of our efforts to develop coastal marine ecosystem management and conservation in the Banting coastal area. Further ecotoxicological studies to establish the potential biomonitors as good heavy metal pollution in the coastal waters of Banting are highly recommended.